ANALISIS PERSEPSI DAN HARAPAN KONSUMEN TERHADAP MAL SURYA BANTEN (STUDI KASUS PADA RENCANA RENOVASI DAN PERUBAHAN KONSEP MAL) - Stivenes Tjin Siam; Genoveva Genoveva (President University, 2016)
Banten Surya mall has been established since 2006 with the specific tenants, especially for supply the factory around Banten. Although it has been established 9 years ago, tenants who rent a shop in the mall is still relatively small at only 10%, because of this condition, the mall owner wants to renovate and simultaneously changing the concept of the mall to better suit the needs of the people in the surrounding area of the mall. Based on the questionnaire distributed to 200 respondents and contained 150 valid questionnaires, the satisfaction of respondents to the mall was low and not in accordance with the expectations of respondents, so after visiting the mall, the respondent did not come back because they do not meet their expectations. Respondents expect that the mall can provide their needs, such as foods, daily product, cloths, and others. By knowing the perceptions and expectations of respondents and at the same time knowing the competitors malls around Banten today, Banten Surya mall management is expected to be able to renovate and change the concept of the mall.